Arctic counterterrorism: can Arctic cooperation overcome its most divisive challenge yet?. Issue 1 (2nd January 2019) - Elgsaas, Ingvill Moe
ABSTRACT: This article examines the potential for international cooperation in Arctic counterterrorism. Focus is on cooperation involving Russia and its immediate Arctic neighbours, the United States and Norway. The article discusses the evolution of hard security cooperation in the Arctic through freezes and thaws in international relations. It further discusses cooperation between Russia and NATO in the global war on terror, and how this common cause turned into a core for contention. The article draws attention to two fundamental and critical impediments to international cooperation in Arctic counterterrorism: aversion to information sharing and the problem of labelling terrorists. Throughout its discussions, the article illustrates lingering trust issues between Russia and its Western neighbours. This mistrust underscores challenges to hard security cooperation among the Arctic states in general, and to cooperation in the highly politicised field of counterterrorism in particular. Abbreviation : NATO: North Atlantic Treaty Organization; OSCE: Organization for Security and Co-operation in Europe; CSIS: Center for Strategic and International Studies; SAR: search and rescue; OSR: oil spill response; STANDEX: Stand-off Detection of Explosives; CAI: Cooperative Airspace Initiative; US: United States, HQ: headquarters; UN: United Nations, ISIS: Islamic State of Iraq and Syria